Carbohydrate Intake is Associated with Learning Concentration among High School Students in Jember Regency, East Java Province, Indonesia - Nadya Parahita Handini; Triyanti Triyanti; Kusharisupeni Kusharisupeni (Faculty of Public Health Universitas Indonesia, 2022)
This study aims to determine the relationship between learning concentration and several factors and to find themostdominantfactorinthestudentsofSMAN1Jember.Inthisstudy,learningconcentrationwasthedependentvariable,whilebreakfasthabits,nutrientintake(energy,carbohydrates,protein,fat,iron,zinc,vitamin B12, vitamin C), sleep quality, and physical activity were independent variables. This research is aquantitativestudy with cross-sectional design. This study conducted in June 2021 at SMAN 1 Jemberwith atotal of200 respondents who were selected using the quota sampling method. Data were collected throughfilling out online questionnaires. The data obtained were analyzed using univariate, bivariate analysis using chi-square,andmultivariateanalysisusingmultiplelogisticregression.Theresultsshowthat52.5%oftherespondents had a high learning concentration. The results also show that breakfast habits (p=0,016), energyintake(p=0,037),carbohydratesintake(p=0,000),andsleepquality(p=0,020)arerelatedtolearningconcentration among adolescents. The results of multivariate analysis showed that carbohydrate intake was thedominantfactor associatedwithlearningconcentrationinadolescents.